2014
DOI: 10.1007/s11033-014-3523-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of three X-linked tetrameric microsatellite markers for forensic purposes

Abstract: In this study, we obtained sequence and population genetic data for three X-linked short tandem repeat markers (X-STRs; DXS7129, DXS2500, G10583). We investigated their population genetics and estimated their forensic parameters in 214 healthy unrelated individuals from the Han population of Northern China (105 males and 109 females). We showed that DXS2500 and G10583 were highly polymorphic and thus have potential for application in forensic medicine. We also estimated the overall linkage disequilibrium betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…However, autosomal STRs may not be effective in some deficiency paternity cases, such as the father–daughter testing that the DNA of mother is not available, and the full sisters or paternal sisters testing that the DNA of their biological father is not available. X‐chromosomal STRs were proved to be effective in these cases , because one of two X‐chromosomes of daughter is certainly inherited from her biological father and the sisters share the same paternal X‐chromosome. However, only several studies were reported with some available multiplex amplification systems, including Mentype® Argus X‐8 kit (Biotype AG, Dresden, Germany), Investigator Argus X‐12 (Qiagen, Hilden, Germany) and ZJGA‐X12 STR kit (AGCU ScienTech, Wuxi, Jiangsu, China) in the past .…”
Section: Introductionmentioning
confidence: 99%
“…However, autosomal STRs may not be effective in some deficiency paternity cases, such as the father–daughter testing that the DNA of mother is not available, and the full sisters or paternal sisters testing that the DNA of their biological father is not available. X‐chromosomal STRs were proved to be effective in these cases , because one of two X‐chromosomes of daughter is certainly inherited from her biological father and the sisters share the same paternal X‐chromosome. However, only several studies were reported with some available multiplex amplification systems, including Mentype® Argus X‐8 kit (Biotype AG, Dresden, Germany), Investigator Argus X‐12 (Qiagen, Hilden, Germany) and ZJGA‐X12 STR kit (AGCU ScienTech, Wuxi, Jiangsu, China) in the past .…”
Section: Introductionmentioning
confidence: 99%